The Effect of Electronic Word of Mouth, Brand Image, and Celebrity Endorsement on Interest in Buying Scarlett Whitening Products - Sofiyaranti, Sofiyaranti; Jumai , Jumai (Economics and Business International Conference Proceeding, 2024)
This study aims to determine how the influence of Electronic Word of Mouth, Brand Image, and Celebrity Endorsement on Buying Interest in Scarlett Whitening Products (Study on Generation Z People in Tembalang District). This study uses a quantitative approach using primary data obtained from distributing questionnaires to respondents via google form. The sampling technique used was purposive sampling, the number of samples used was 100 people using the Lemeshow formula. The method of analysis in this study is multiple linear regression analysis with the help of the SPSS version 25 program: (1) Electronic Word of Mouth has a positive and significant effect on purchase intention of Scarlett Whitening. (2) Brand Image has a positive but insignificant effect on buying interest in Scarlett Whitening. (3) Celebrity Endorsement has a positive but insignificant effect on buying interest in Scarlett Whitening. (4) Electronic Word of Mouth, Brand Image, and Celebrity Endorsement simultaneously have a positive and significant impact on Scarlett Whitening Purchase Intention.